2012
DOI: 10.5539/cis.v6n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Citation Frequencies of Leading Software Engineering Scholars

Abstract: It is understandable that sponsors of research activities are interested in assessing the work of scholars they (plan to) support although this is not a simple undertaking. Until today, there is no obvious approach for objectively measuring and comparing the quality of research results from different disciplines. Hence, counting publications has been used for long time as a substitute to deal with this challenge and only recent technological advances have fostered the usage of so-called citation indices (such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The h-index of an author is then equal to the rank where the number of citations is at least as large as the rank. As an example consider the h-index of Barry Boehm in late 2011, where this was the case on rank 53 as shown in TABLE III on the next page (data taken from Hummel et al [13]). …”
Section: Our Approach: One Results Per Ensemblementioning
confidence: 98%
“…The h-index of an author is then equal to the rank where the number of citations is at least as large as the rank. As an example consider the h-index of Barry Boehm in late 2011, where this was the case on rank 53 as shown in TABLE III on the next page (data taken from Hummel et al [13]). …”
Section: Our Approach: One Results Per Ensemblementioning
confidence: 98%
“…Since these studies were localized to a certain country, it explored lesser number of papers Citation based studies have also evolved into adoption of measures such as h-index and g-index to study the success of an SE researcher. Hummel et al in 2013 analyzed the expressiveness of modern citation analysis approaches like h-index and g-index by analyzing the work of almost 700 researchers in SE [25]. They concluded that on an average h-index for a top author is around 60 and g-index is about 130.…”
Section: Bibliometrics Based Studiesmentioning
confidence: 99%
“…For another, several bibliometric studies attempted to identify not top papers but top scholars and institutions in the field of software engineering in various geographies. Garousi and Varma [24], for instance, performed such an analysis for Canada, whereas Hummel et al [32] took a global approach and ranked highly influential software engineering scholars who were program committee or organizing committee members of reputable software engineering venues or ACM SIGSOFT research award winners. Other authors fused these two substreams of research, reporting on both top papers and scholars [14].…”
Section: Background and Related Workmentioning
confidence: 99%